2013
DOI: 10.1590/s0104-66322013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of orange bagasse and molokhia stalk for production of pectinase enzyme

Abstract: -Studies were conducted on the production and extraction of exo-polygalacturonase (PG) in solidstate fermentation (SSF) using orange bagasse (Ob) and molokhia stalks (Ms) as a new solid support by Penicillium pinophlilum Hedg 3503 NRRL. The parameters affecting PG production under SSF were optimized. The maximum PG activity of ~ 3270 U/ g dry solid substrate was obtained from P. pinophlilum Hedg 3503 NRRL grown for 7 days on Ob and Ms in the ratio 1:3 (w/w), moistened with distilled water at 68.2% initial mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Pedrolli and Carmona (2008) observed A. giganteus produced significant pectin lyase activity in medium with orange waste contents, with peak production at 2% (wv-1) [54]. According to Ahmed and Mostafa (2013), orange bagasse constitutes an excellent inducer substrate for PGase production by P. pinophilum Hedg NRRL 3503, which represented 69.20% increase in enzyme production compared with control [6]. Ahmed and coauthors showed maximum enzyme activity under optimum orange peel concentration of 4% for pectinase production by A. niger [55].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Pedrolli and Carmona (2008) observed A. giganteus produced significant pectin lyase activity in medium with orange waste contents, with peak production at 2% (wv-1) [54]. According to Ahmed and Mostafa (2013), orange bagasse constitutes an excellent inducer substrate for PGase production by P. pinophilum Hedg NRRL 3503, which represented 69.20% increase in enzyme production compared with control [6]. Ahmed and coauthors showed maximum enzyme activity under optimum orange peel concentration of 4% for pectinase production by A. niger [55].…”
Section: Discussionmentioning
confidence: 94%
“…The strain was cultivated in the RF medium, containing 4% (wv-1) of each agro-industrial waste, instead of commercial citrus pectin. The fermentations were carried out as mentioned above, and experiment runs in the original culture medium (RF) were considered as control [6,8,36].…”
Section: Selection Of a Pectin-containing Materials As Inductor For Pgmentioning
confidence: 99%
See 1 more Smart Citation
“…Dhillon et al [208] achieved higher citric acid extraction from the SSF process using response surface methodology involving process parameters such as extraction time, agitation rate, and solvent volume. Solid-liquid ratio, solvent or buffer type, pH, temperature, stirring rate, repeated extraction, and extraction time are process parameters that also have been studied to optimize the extraction of products from SSF [209][210][211][212][213][214]. However, in these studies usually a small amount of solid substrate ranging from 1-20 g in a shake flask was used for the extraction, and only some of them reported the extraction using the whole substrate fermented (in kg) with the aim of knowing the total recovery of the product [20].…”
Section: Downstream Processing In Ssf and Residue Reutilizationmentioning
confidence: 99%
“…Pectinase production used in industry has been reported from microorganisms including bacteria (Swain and Ray, 2010;Roosdiana et al, 2013), actinomycetes (Kuhad et al, 2004;Jacob and Prema, 2006), filamentous fungi in particular of the Aspergillus niger (Solis-Pereira et al, 1993), Penicillium pinophlilum (Ahmed and Mostafa, 2013), Penicillium viridicatum (Silva et al, 2002), Mucor circinelloides (Thakur et al, 2010) and some yeast (da Silva et al, 2005;Oliveira et al, 2006;Serrat et al, 2011;Taskin, 2013). Aspergillus niger is known worldwide for production of secondary metabolites and extracellular enzymes of commercial value, including industrial production of pectinases Yeasts have advantages compared to filamentous fungi with regard to the production of pectinases, because they are unicellular, the growth is relatively simple and the growth medium does not require an inducer.…”
Section: Introductionmentioning
confidence: 99%